2020
DOI: 10.1186/s11556-020-00251-9
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and physical functioning: a cross-sectional multimethod facet-level analysis

Abstract: Background This study aimed to investigate whether personality traits and their facets are associated with a multi-methods assessment of physical activity and walking performance and whether they explain the discrepancy between self-reported and accelerometer-assessed physical activity. Methods The participants were community-dwelling, 70–85-year-old men and women from Finland (n = 239) who were part of a clinical trial. Personality traits and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In the same study, however, extraversion was not associated with discrepancy between self-reported and accelerometer-measured leisure time physical activity. Another study on physical activity showed that open individuals tended to overestimate their self-reported physical activity compared to accelerometers (Kekäläinen, Terracciano, et al, 2020). Of note, Kekäläinen, Terracciano, et al (2020) did not only focus on personality traits but also considered their facets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, however, extraversion was not associated with discrepancy between self-reported and accelerometer-measured leisure time physical activity. Another study on physical activity showed that open individuals tended to overestimate their self-reported physical activity compared to accelerometers (Kekäläinen, Terracciano, et al, 2020). Of note, Kekäläinen, Terracciano, et al (2020) did not only focus on personality traits but also considered their facets.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on physical activity showed that open individuals tended to overestimate their self-reported physical activity compared to accelerometers (Kekäläinen, Terracciano, et al, 2020). Of note, Kekäläinen, Terracciano, et al (2020) did not only focus on personality traits but also considered their facets. Analyses at the more granular facet level revealed further insights, such that the effect of openness was mainly driven by the facets “fantasy” and “ideas,” and that individuals who scored high on the “excitement-seeking” facet of extraversion also overestimated their physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Given these associations with stress and health-related behaviors, it is not surprising that personality traits are also related to better health, function, and longevity (27, 29, 34, 4750). We observed a positive association between mtDNAcn and personality traits that are also related to health-relevant habits and conditions, such as non-smoking (51), healthy diet and obesity (52, 53), exercise and physical function (54), and preventive medical screenings (55). Thus, indirect pathways may exist to link personality and health-related behaviors to changes in mitochondrial biology.…”
Section: Discussionmentioning
confidence: 92%
“…A significant positive covariance was observed between walking and S/LIE, and between S/LIE and MSE. It has been reported that people with personality traits, such as extroversion and conscientiousness, are more active [ 41 ], and that the presence or absence of these traits may act as hidden common factors. Otherwise, the covariance between walking and paid work is negative.…”
Section: Discussionmentioning
confidence: 99%